2021
DOI: 10.1002/stem.3457
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Regulates Adult Neurogenesis in the Ventricular-Subventricular Zone via Dopamine D3 Angiotensin Type 2 Receptor Interactions

Abstract: Adult neurogenesis is a dynamic and highly regulated process, and different studies suggest that dopamine modulates ventricular-subventricular zone (V-SVZ) neurogenesis. However, the specific role of dopamine and the mechanisms/factors underlying its effects on physiological and pathological conditions such as Parkinson's disease (PD) are not fully understood. Recent studies have described counter-regulatory interactions between renin-angiotensin system (RAS) and dopamine in peripheral tissues and in the nigro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…We showed that HAL was able to suppress the inhibitory effect of MK-801 on DCX . Previous studies have shown that dopamine positively regulates cell proliferation, and proliferation decreases after dopamine depletion can be reversed by dopamine stimulation in vivo [ 40 ]. Dopamine is able to modulate NMDA receptor activity, and D2 receptors have been shown to reduce NMDA receptor activity and neuronal calcium influx [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that HAL was able to suppress the inhibitory effect of MK-801 on DCX . Previous studies have shown that dopamine positively regulates cell proliferation, and proliferation decreases after dopamine depletion can be reversed by dopamine stimulation in vivo [ 40 ]. Dopamine is able to modulate NMDA receptor activity, and D2 receptors have been shown to reduce NMDA receptor activity and neuronal calcium influx [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that the deletion of the Shh receptor Smoothened (SMO) in Glial fibrillary acidic protein (GFAP) positive NSCs at the perinatal stage leads to premature aging-related decline of adult neurogenesis ( Wang et al., 2022 ). DA neuron projections have been described at the SVZ region where the adult neural stem cells reside and have been suggested to regulate SVZ neurogenesis through the release of factors such as dopamine ( Garcia-Garrote et al., 2021 ; Hoglinger et al., 2004 ). Therefore, we decided to examine whether DA neuron projections from the midbrain to the STR/SVZ region could be a critical source of SHH ligand for maintaining Shh signaling in NSCs.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have reported that abolishing Shh signaling in the mGFAPcre mouse line results in decreased adult neurogenesis in both the SVZ and SGZ, and our recent study shows that Shh KO further accelerates the age-related decline in adult neurogenesis and contributes to increased anxiety in mGFAP-smo cKO mice ( Wang et al., 2022 ). As SN DA neuron projections have been previously reported to regulate SVZ NSCs at least partially through the release of dopamine ( Garcia-Garrote et al., 2021 ; Hoglinger et al., 2004 ), we examined whether midbrain DA neuron projections could potentially provide SHH ligand to the SVZ NSCs in order to maintain their homeostasis. However, our data show that at 3 months of age, there is no difference in either the population of proliferating cells (Ki67+) or newly differentiated neuroblasts (DCX+) in the SVZ, suggesting midbrain DA neuron projections are not a critical source for maintaining Shh signaling in SVZ NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The neurotransmitters dopamine and serotonin have been found to have positive effects on neurogenesis and proliferation within the CNS. [8][9][10][11][12][13][14] For instance, some research groups reported that the neurotransmitter dopamine plays a role in regulating endogenous neurogenesis in the adult mammalian brain such as in the ventricular-subventricular zone (V-SVZ). 9,15 The counter-regulatory interactions between the renin-angiotensin system and dopamine in peripheral tissues and in the nigrostriatal system have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] For instance, some research groups reported that the neurotransmitter dopamine plays a role in regulating endogenous neurogenesis in the adult mammalian brain such as in the ventricular-subventricular zone (V-SVZ). 9,15 The counter-regulatory interactions between the renin-angiotensin system and dopamine in peripheral tissues and in the nigrostriatal system have been reported. However, the specific role of dopamine and the mechanisms underlying its effects on physiological and pathological conditions such as neurodegenerative diseases remain unclear.…”
Section: Introductionmentioning
confidence: 99%